Education and Territory: The Family and Sociocultural Environment in Rural Contexts as a Possible Cause of University Dropout - Fabiola, Ávila Martínez María; Alberto, Zambrano Ureta Luis; Antonio, Navarrete Schettini Gabriel; Intriago, Jonathan Gerardo Chicaiza; Armandina, Álava Chávarria (Journal of Ecohumanism, 2025)
This research examines university dropout in rural contexts, using the Tigre II community in Manabí, Ecuador, as a case study. Through a mixed-methods approach, the community context was characterized, family dynamics and sociocultural factors were evaluated, and strategies to mitigate educational abandonment were designed. Surveys, interviews, and evaluation matrices (EFI, EFE, and INCIDE) were applied, revealing low academic expectations within households, the influence of traditional gender roles, limited educational and technological infrastructure, and weak connections between families and the university system. The findings allowed for the prioritization of critical dropout factors and the validation of intervention strategies such as e-mentoring and family digital literacy. The study concludes that in rural settings, family and sociocultural environments significantly influence and increase the likelihood of university dropout, exacerbated by a web of structural and symbolic conditions that require contextualized, comprehensive, and sustainable actions.